Health and Well-Being of Athletes During the Coronavirus Pandemic: A Scoping Review - Raven Haan; Mariyam Essa Ali Alblooshi; Dawood Hasan Syed; Khaled Khalifa Dougman; Hashel Al Tunaiji; Luciana Aparecida Campos; Luciana Aparecida Campos; Luciana Aparecida Campos; Ovidiu Constantin Baltatu; Ovidiu Constantin Baltatu; Ovidiu Constantin Baltatu (Frontiers Media S.A., 2021)
Background: The ongoing global pandemic has become the world's leading health problem, causing massive public fear and concern. Reports suggest that athletes are seeking mental health support, showing the pressures of boredom, and tension associated with their anticipated social isolation. The current study seeks to evaluate the evidence regarding the effects of the coronavirus pandemic on occupational stress in professional athletes.Method: A scoping review was conducted. A comprehensive search involving Embase and PubMed databases was conducted using a combination of the following key words: COVID-19, SARS-CoV-2, coronavirus, and athletes. In this study, articles were retained if they were original studies reporting on the impact of the pandemic on professional athletes.Results: Nine studies were identified as they investigated the impact of the pandemic on athletes. Most were observational and cross-sectional, and one was longitudinal. Outcome measures mainly investigated were level of depression, anxiety, and stress. Dependent variables were physical activity, nutrition, mental state, sleep quality, individual well-being, social identity, exclusivity, negative affectivity, alcohol consumption, psychological distress, and gambling habits.Conclusions: This review highlights the need for proactive engagement with professional athletes, coaches, trainers, and sports councils to facilitate understanding and awareness-raising, process optimization, and delivery of consistent training and psychosocial aid and occupational therapy programs that maintain the health and well-being of athletes while minimizing occupational stress during a pandemic.